Mitochondrial DNA Levels are not a simple indicator for preselection of Euploid Embrios with higher developmental potential. (April 2019) - Rechistsky, Svetlana; Cram, David; Leigh, Don; Cao, Yanan; Wang, Li; Yao, Yuanqing; Kuliev, Anver
Abstract : Objective: Previous studies suggested that high mtDNA levels may be used for identification of euploid embryos with poor developmental competence. This does agree with the other observations on the relationship of high mtDNA levels to poor implantation potential, observable in embryos at the cleavage and blastocyst stage, despite using different approaches in estimating the mtDNA levels, suggesting a possibility of some underlying errors in the measurements of mtDNA copy number in different studies. We present here the data of a blinded retrospective analysis of the reproductive outcomes of euploid embryo transfers, depending on mtDNA levels, performed by identical methodology in two different groups of patients in two different clinics. Materials and Methods: Two independent PGT clinics performed this retrospective re-analysis of mtDNA levels following single blastocyst transfers (group A, n=49; group B, n=70) or double blastocyst transfers (group A, n=36; group B n=29). The mtDNA levels were correlated with implantation, miscarriage and live-birth. Aneuploidy testing was performed by NGS and the data was used to calculate the mtDNA/gDNA ratio (mtDNA ratio), expressed as the number of mapped mtDNA sequencing reads x 100%/ number of mapped autosomal sequencing reads. Results: Only embryos identified as euploid and suitable for transfer were analyzed. Implantation rates for single embryo transfers were 43% (group A) and 55% (group B) and for double embryo transfers 54% (group A) and 62% (group B). Overall, the average mtDNA ratio was 0.018% with a range of 0.002% to 0.14%. For the single embryo transfer groups, there was no significant difference for the average mtDNA ratio, or the mtDNA ratio profile of the pregnant and non-pregnant women. Amongst both pregnant groups, there was no obvious correlation of mtDNA ratios with the miscarriage subgroup and those with a continuing, successful pregnancy. Further, there was no obvious trend between the mtDNA ratio and twin delivery, singleton delivery, miscarriage or failure to implant. Conclusions: The study could not support the findings suggesting that highmtDNA ratios are an indicator of implantation failure. The results show that the mtDNA ratio of trophectoderm biopsy samples cannot be used as an additional parameter for pre-selection of euploid embryos for transfer.